Tropical cyclone and related meteorological data sets available at CSU and their utilization - Gray, W. M., author; Buzzell, E., author; Burton, G., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1982)
This report has been prepared to familiarize the international meteorological community with the comprehensive collection of tropical cyclone and other meteorological data which are available on our research project. We provide a rationale for the research philosophy behind the assembling of these data sets over the last decade, describe the data and indicate how other researchers may use them for their own the research purposes. In particular, we summarize the rawindsonde compositing philosophy and the other research techniques employed on our project. We describe our data processing procedures, the various formulations we have used for different research purposes, the coordinate systems employed and the data availability by region. Our research accomplishments, types of compositing runs, and a list of publications are also presented. These data sets and their software support represent a considerable manpower and financial investment. An investment that is now able (we believe) to provide a high return in the form of new knowledge on tropical cyclones and other weather systems. We are currently exploring a number of exciting avenues. The possibilities are quite broad and we encourage other research workers to help exploit this resource.
February, 1982.
Keywords: Colorado State University. Department of Atmospheric Science; Cyclones -- Tropics -- Observations; Tropical meteorology -- Data processing; Meteorology -- Research -- Colorado